Development and Characterization of Pullulan-Carboxymethyl Cellulose Blend Film for Packaging Applications - Murugesan Thangavelu; Senthil Vadivu Kulandhaivelu (International Journal of Polymer Science)
Edible packaging materials have widespread applications in pharmaceutical industries. In this study, the physical, thermal, colour, mechanical, and water barrier properties of a novel edible film based on pullulan (PUL) and carboxymethyl cellulose (CMC) were investigated. The blend films were made by the solution casting method with 3 g of total solid content. The following percentages of 100/0, 75/25, 50/50, 25/75, and 0/100 were used to prepare the films. Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA) were used to analyze the interaction between PUL and CMC. At the level of 75/25 percentage of PUL, CMC film showed the lowest EAB% (5.55%), the highest values for TS (17.30 MPa), WVP value (4.12×10−10 g m-1s-1Pa-1), and water contact angle of 63.43°. By increasing the CMC concentration, blend films became slightly greenish and yellowish but appeared transparent with UV blocking ability. This study reveals that 75/25 (PUL/CMC) blend film has a good potential that can be used in producing edible packaging films to protect the quality of pharmaceutical products with interesting specifications.